On the commutant of a multiplication operator and conditions of invertibility of its elements - Berezovsky, N. I.; Linchuk, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We obtain a description of isomorphisms acting in the space of square summable functions and commuting with the operator of multiplication by a continuous piecewise monotone function. Preliminary corrections are made of some mistakes found in the statements of the paper [3].